Compressive strength and microstructural evolution of metakaolin geopolymers exposed at high temperature - Burciaga-Díaz, O.; Escalante-García, J. I.; Magallanes-Rivera, R. X. (Revista ALCONPAT, 2015)
This research presents results of compressive strength and microstructural evolution of geopolymers exposed to high temperatures. Pastes of molar were elaborated blending metakaolin and sodium silicate solutions containing NaOH. The effect of the composition on the development of compressive strength was investigated and pastes were chosen to be exposed to 200, 500 and 800 °C, characterizing their microstructure and compressive strength. Before to high temperature exposure, the binders developed 80MPa, and after their exposition, the loss of strength depended of the ratio SiO2/Al2O3. Results of XRD, FT-IR and SEM suggest that the reorganization of the silica gel and the water evaporation reduce the thermal stability of samples exposed to high temperature. Keywords: Geopolymers, metakaolin, thermal performance, compressive strength, microstructures.